Direct Measurement of Ab in Z0 decays using charged kaon tagging - Abe, K; Abe, T; Adam, I; Akagi, T; Allen, N; Arodzero, A; Ash, W; Aston, D; Baird, K; Baltay, C; Band, H; Barakat, M; et al. (1999)
We present a direct measurement of the_parity-violating asymmetry Ab, in the Z0 to bb̄ coupling using a new technique to distinguish the b and b̄ quarks using charged kaons from B decays. The Z0 bosons are produced in e+e- collisions at the SLC with longitudinally polarized electrons, bb̄ events are selected using a secondary vertex mass tag and Ab is determined from the left-right forward-backward asymmetry. From the 1994-1995 data sample, selected from 100000 hadronic Z0 decays, we obtain Ab = 0.855 ± 0.088stal ± 0.102syst. © 1999 The American Physical Society.